2017
DOI: 10.1021/acsami.7b15116
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite as a Vehicle for the Selective Effect of Superparamagnetic Iron Oxide Nanoparticles against Human Glioblastoma Cells

Abstract: Despite the early promises of magnetic hyperthermia (MH) as a method for treating cancer, it has been stagnating in the past decade. Some of the reasons for the low effectiveness of superparamagnetic nanoparticles (SPIONs) in MH treatments include (a) low uptake in cancer cells; (b) generation of reactive oxygen species that cause harm to the healthy cells; (c) undeveloped targeting potential; and (d) lack of temperature sensitivity between cancer cells and healthy cells. Here we show that healthy cells, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 111 publications
3
25
0
Order By: Relevance
“…Previous reports indicated that labeling with Fe 3 O 4 nanohybrids increases MSC viability, 42 whereas use of commercial iron oxide nanoparticles (ie, magnetic iron oxide beads) reduces viability. 45 In the present study, we observed similar rates of MSC proliferation as those of unlabeled control MSCs, which agreed with previously reported results, [50][51][52][53] however, some previous studies indicated that uptake of iron oxide nanoparticles stimulated in vitro MSC proliferation but reduced CFU. 54,55 These conflicting results might be associated with differences in nanoparticles size, shape, surface modification, incubation concentration, and time.…”
Section: Effect Of Iron Oxide Nanoparticles On Msc Viability and Prolsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous reports indicated that labeling with Fe 3 O 4 nanohybrids increases MSC viability, 42 whereas use of commercial iron oxide nanoparticles (ie, magnetic iron oxide beads) reduces viability. 45 In the present study, we observed similar rates of MSC proliferation as those of unlabeled control MSCs, which agreed with previously reported results, [50][51][52][53] however, some previous studies indicated that uptake of iron oxide nanoparticles stimulated in vitro MSC proliferation but reduced CFU. 54,55 These conflicting results might be associated with differences in nanoparticles size, shape, surface modification, incubation concentration, and time.…”
Section: Effect Of Iron Oxide Nanoparticles On Msc Viability and Prolsupporting
confidence: 93%
“…Numerous studies have described flow cytometric evaluation of MSC surface markers in order to assess the differentiation potential of MSCs following nanoparticle internalization. 35,[45][46][47][48][49] In agreement with our findings, their results consistently reported no effects on surface-marker expression or osteogenic and adipogenic differentiation ability. These results showed that nanoparticlelabeling did not alter MSC differentiation or characteristics higher than 50 µg/mL did not enhance cell-uptake efficiency, at 100 µg/mL, the nanoparticles tended to aggregate in the culture medium and adhere to the plate.…”
Section: Characterization Of Mscs Loaded With Iron Oxide Nanoparticlessupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the SPION zeta potential was −10 mV, a value that might not favor the SPION internalization by cells [81]. Another study that synthesized aminosilane-coated SPION, they were submitted to low frequency (1.16 uT and 350 kHz) and a single MHT application for 30 min, showing 30% of K7M2 cells viability by BLI 24 h after finished the therapy [34], and others studies that used single MHT therapy application displayed efficiency superior than 50% [32,35].…”
Section: Discussionmentioning
confidence: 69%
“…MHT therapy outcome evaluation has been reported by different approaches using conventional techniques as follows: trypan blue [19,32,33], MTT [19,[34][35][36], tunnel assay [32], live/dead assay [37,38], and Western blot [32] that in most cases have limitations for longitudinal analysis.…”
Section: Introductionmentioning
confidence: 99%